Diversity of the Crinocheta (Crustacea, Isopoda, Oniscidea) from Early Miocene Chiapas amber, Mexico - Pierre Broly; María de Lourdes Serrano-Sánchez; Francisco J. Vega (Revista Mexicana de Ciencias Geológicas)
Currently, the Onisicdea (terrestrial isopods) is a massive Crustacea suborder of more than 3 700 species, but our knowledge of their paleodiversity is poor. In this paper, we present ten fossils of Crinocheta, the largest clade within the Onisicdea, discovered in Early Miocene (23 Ma) amber of Chiapas. We described three new genera and six new species including Palaeolibrinus spinicornis gen. nov. sp. nov., Armadilloniscus miocaenicus sp. nov., Archeostenoniscus robustus gen. nov. sp. nov., Archeostenoniscus mexicanus sp. nov., Palaeospherarmadillo mazanticus gen. nov. sp. nov., and Palaeospherarmadillo rotundus sp. nov. This study represents the first fossil record of the family Detonidae, Olibrinidae, and “Stenoniscidae”. From a paleoenvironmental reconstruction perspective, the oniscidean fauna presented here supports a particularly wet paleoenvironment, under brackish water influence, similar to an estuary.